Evaluation of frozen section margins in high‐risk cutaneous squamous cell carcinomas of the head and neck. (17th September 2014) - Chambers, Kyle J.; Kraft, Stefan; Emerick, Kevin
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To identify histopathologic features associated with poor correlation of frozen and permanent pathology margins following wide local excision for advanced cutaneous squamous cell carcinomas of the head and neck. Study Design Retrospective review. Methods A retrospective review of patients undergoing excision of advanced head and neck squamous cell carcinomas between the years 2010 AND 2013 was performed. Demographic, operative, and pathology data were collected. Overall correlation between frozen section margins and final margins on permanent section results was calculated. Positive and negative predictive values of several histopathologic features were determined. Results Forty‐one cases were identified from the database. Perineural invasion, lymphovascular invasion, and a component of poorly differentiated carcinoma were identified in 61.3%, 34.5%, and 17.1% of cases, respectively. Discrepancy between frozen section margins and permanent margins was identified in eight cases (19.5%). The false‐negative rate for poorly differentiated carcinoma, lymphovascular invasion, and perineural invasion was 14%, 36%, 26%, respectively. The positive and negative predictive value of poorly differentiated carcinoma, lymphovascular invasion, and perineural invasion in predicting discrepancy between frozen and permanent margins was 14% and 80%, 36% and 84%, and 26% and 92%, respectively. Conclusions This study demonstrated a moderate rate of discrepancy between frozen and permanent section analysis of operative margins from high‐risk cutaneous squamous cell carcinomas of the head and neck. The presence or absence of certain histopathologic features appears to be associated with a higher rate of frozen section discrepancy. Evaluation of these features in a preoperative biopsy or staging excision may be useful in planning definitive excision and reconstruction. Level of Evidence 4 Laryngoscope, 125:636–639, 2015